Constraints Faced by Farmers in Adoption of Guava Production Technology in Tikamgarh District of Madhya Pradesh - V. K. Singh; P. K. Tyagi (Indian Journal of Extension Education, 2017)
The study was undertaken in Tikamgarh district of Madhya Pradesh to investigate the constraints faced by guava growers during production and marketing of guava and document the suggestions offered in adoption of guava production technology. The constraints which were most perceived by guava growers were unavailability of quality planting material, lack of proper post harvest management facilities and lack of knowledge about varieties suitable to their areas. Farmers offered suggestions for ensuring quality planting material